Online Learning Quality Evaluation in Higher Education During COVID-19 Pandemic: Evaluasi Kualitas Pembelajaran Daring di Perguruan Tinggi Selama Pandemi COVID-19 - Suharyat, Yayat; Susilawati, Tri Elsa; Sikki, Muhammad Ilyas; Nurhayati, Sri (Society, 2022)
The COVID-19 pandemic has drastically altered people’s lives, including university education. COVID-19 has significantly impacted the transition from offline to online learning. Furthermore, education in Indonesia must be able to accelerate education 4.0. The learning system is carried out remotely using information technology. There will be numerous major challenges in implementing the online learning model. During the COVID-19 pandemic, Universitas Islam 45 needed to assess student satisfaction with online learning to maintain service quality. This study aimed to assess student satisfaction during online learning during the COVID-19 pandemic using the Service Quality (Servqual) and Importance Performance Analysis (IPA) methods. Servqual and IPA are methods for measuring customer satisfaction and service quality. According to the Servqual results, all 17 measurements have a negative gap value. This demonstrates a gap between students’ perceptions and expectations of online learning. The IPA Matrix indicates the priority of improving online-based learning, which includes responding quickly and efficiently to students’ needs in online-based learning, encouraging students’ motivation throughout the learning process, and understanding students’ impediments during the process of online-based learning.